A Guide to Automating the Histology Laboratory. Issue 8 (16th December 2015) - Gamble, Marilyn
Abstract : Histopathology has somewhat mirrored the rest of the clinical laboratory through the incorporation of automation to replace manual steps. When researched and implemented, automation can streamline the overall process and result in a more efficient, standardized, and costeffective operation. This article describes equipment, identifies considerations for implementation into your laboratory, and lists sources and estimated price ranges.